Psycho therapy [videorecording (DVD)] : the shallow tale of a writer who decided to write about a serial killer - Karaçelik, Tolga, 1981-; Buscemi, Steve, 1957-; Magaro, John, 1983-; Lower, Britt, 1985- (Brainstorm Media, 2025)
Masquerading as a marriage counselor, a serial killer teaches his methods to a desperate writer trying to find inspiration and save his marriage.